2009
DOI: 10.1136/bjsm.2008.056457
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lateral epicondylitis using skin-derived tenocyte-like cells

Abstract: Skin-derived tenocyte-like cells can be cultured in the laboratory to yield a rich preparation of collagen-producing cells. Our pilot study suggests that these collagen-producing cells can be injected safely into patients and may have therapeutic value in patients with refractory lateral epicondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 32 publications
1
130
0
Order By: Relevance
“…Another study of 60 patients with patellar tendinopathy noted clinical improvement in a group treated with MSCs injections [11]. The study was supported by Ultrasound examination and revealed reduction in tendon thickness after stem cells therapy.…”
Section: Healing Of the Tendonmentioning
confidence: 57%
See 1 more Smart Citation
“…Another study of 60 patients with patellar tendinopathy noted clinical improvement in a group treated with MSCs injections [11]. The study was supported by Ultrasound examination and revealed reduction in tendon thickness after stem cells therapy.…”
Section: Healing Of the Tendonmentioning
confidence: 57%
“…Ultrasound controlled study of lateral epicondylitis on 12 patients showed positive outcomes in clinical and ultrasonographic scale [11]. Another study of 60 patients with patellar tendinopathy noted clinical improvement in a group treated with MSCs injections [11].…”
Section: Healing Of the Tendonmentioning
confidence: 99%
“…A pilot study of 12 patients with refractory elbow epicondylitis treated with collagen producing cells derived from dermal fibroblasts showed a significant improvement in the patient-rated tennis elbow evaluation scale and ultrasound tendon appearance [88].…”
Section: Parmacology Of Mscsmentioning
confidence: 99%
“…Future developments are likely to see an increased use of growth factors, mesenchymal stem cells and other derived tenocyte-like cells for treatment of tendon and muscle injury [17,66,67].…”
Section: Other Techniquesmentioning
confidence: 99%